Pengaruh E-Service Quality, E-Satisfaction, dan E-Trust Terhadap E-Loyalty pada Pengguna Aplikasi My BCA di Denpasar - Astiti Utami Devi, Dewa Ayu Kade; Artyanti Putri, Putu Riana (Economic Reviews Journal, 2025)
The advancement of digital technology has driven significant transformation in the banking sector, particularly in the development of electronic-based services. One manifestation of this innovation is the MyBCA application, which allows customers to perform various transactions conveniently. However, factors such as e-service quality, e-satisfaction, and e-trust play crucial roles in shaping electronic loyalty (e-loyalty) among users. This study aims to examine the influence of e-service quality, e-satisfaction, and e-trust on e-loyalty among MyBCA application users in Denpasar City. The research employs a quantitative approach with an associative method. The sample size is determined based on Hair et al. (2010), using ten times the number of indicators, resulting in 180 respondents. Data are collected through a Likert-scale questionnaire and analyzed using SPSS software. The analytical techniques include multiple linear regression analysis, F-test, t-test, and the coefficient of determination (R²). The study is expected to provide theoretical contributions to the development of research on e-loyalty in digital banking and offer practical insights for BCA management to enhance electronic service quality aimed at improving customer loyalty.